Can The Green Board Committee Mitigate ESG Risk? - Muhammad Fadly Agil Rizad; Ahmad Juanda (AFRE (Accounting and Financial Review), 2024)
This research aims to see the influence of determinant factors, namely Green Board Committee, Board Diversity and Firm Size in mitigating ESG Risk Rating. This study uses Regression Robustness Test in data analysis on 79 companies listed on the IDX in 2023 and have ESG Risk Rating. In this study, it was found that the Green Board Committee does not have a significant influence on ESG Risk Rating but must have other variables that can mediate ESG Risk Rating such as ESG activities. then Board Diversity has a significant influence on ESG Risk Rating which means that with diversity in the board of directors, they can have many different perspectives on women who are more sensitive to environmental issues so that they can manage ESG risks well, and Firm Size has a significant influence on ESG Risk Rating which proves that the bigger the company, the more it can manage ESG risks. There are still few studies related to ESG Risk Rating in Indonesia, so it is one of the novelties in this study JEL Classification: G24; M14; M41 DOI: https://doi.org/10.26905/afr.v7i3.14062